2019
DOI: 10.1002/cpt.1338
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety Exposure‐Response Analyses of Olaparib Capsule and Tablet Formulations in Oncology Patients

Abstract: Olaparib is a poly ADP-ribose polymerase inhibitor that induces synthetic lethality in tumors with deficient homologous recombination repair. Population exposure-response analyses were performed to evaluate the efficacy and safety of olaparib exposure in patients with cancer. Data from multiple phase I/II/III clinical studies from both capsule and tablet formulations were combined for efficacy (N = 410) and safety (N = 757) analyses. Exposureprogression-free survival (Cox proportional hazards model indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…In this study, we found a 13% increase and 13% decrease in olaparib C max and a 15% and 8% increase in olaparib AUC seen in patients with mild or moderate hepatic impairment, respectively, vs those with normal hepatic function; these variations in olaparib exposure were not considered clinically relevant 19,20 . Variation in olaparib exposure was notable in the moderate hepatic impairment group; however, this was largely because of 1 patient who had increased exposure to olaparib (indicated by AUC 0–t and C max values; see the Supplementary Materials for further information on this patient).…”
Section: Discussionmentioning
confidence: 66%
“…In this study, we found a 13% increase and 13% decrease in olaparib C max and a 15% and 8% increase in olaparib AUC seen in patients with mild or moderate hepatic impairment, respectively, vs those with normal hepatic function; these variations in olaparib exposure were not considered clinically relevant 19,20 . Variation in olaparib exposure was notable in the moderate hepatic impairment group; however, this was largely because of 1 patient who had increased exposure to olaparib (indicated by AUC 0–t and C max values; see the Supplementary Materials for further information on this patient).…”
Section: Discussionmentioning
confidence: 66%
“…Population pharmacokinetic-pharmacodynamic simulations have suggested that for patients with an AUC > 100 µg h/mL, a clinically significant decrease in haemoglobin may occur, particularly in patients with low baseline haemoglobin. This study has demonstrated that some patients with moderate renal impairment had very high exposure to olaparib (five patients had an AUC > 100 μg h/mL) compared with the mean exposure to olaparib for patients with normal renal function (43.7 μg h/mL) [12]. Patients with very high exposure to olaparib may experience reduced haemoglobin levels and therefore a risk of developing anaemia.…”
Section: Discussionmentioning
confidence: 74%
“…Population pharmacokinetic-pharmacodynamic analyses of 410 patients with ovarian cancer with normal renal function or mild renal impairment evaluated the efficacy (progression-free survival) of olaparib tablets at 300 mg bid and 200 mg bid. The exposure-progression-free survival, Cox proportional hazards model indicated that the 300-mg bid tablet dose was statistically superior to the 200-mg bid tablet dose, although the difference was numerically small [12].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations